Hubungan Tingkat Kecemasan Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe II Di Puskesmas Telaga Dewa Bengkulu - Muhamad Ulga Alhusin; Sulastri Sulastri; Emi Pebriani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
due to impaired insulin secretion and function. In addition to physical impacts, this disease also impacts patients' psychological well-being, including anxiety. Anxiety can trigger a stress response through increased levels of the hormones cortisol and epinephrine, which contribute to elevated blood sugar levels. Data from the Telaga Dewa Community Health Center in Bengkulu shows that the number of Type II Diabetes Mellitus patients continues to increase annually. This study aims to determine the relationship between anxiety levels and blood sugar levels in Type II Diabetes Mellitus patients at the Telaga Dewa Community Health Center in Bengkulu. This study used a descriptive analytical method with a cross-sectional design. The sample size was 68 respondents, using a purposive sampling technique. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), while blood sugar levels were measured using a glucometer. Data were analyzed using univariate and bivariate methods using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents experienced moderate levels of anxiety and had uncontrolled blood sugar levels. Bivariate analysis showed a significant relationship between anxiety levels and blood sugar levels in patients with Type II Diabetes Mellitus. The p-value was 0.000. The conclusion of this study is that there is a relationship between anxiety levels and blood sugar levels in patients with Type II Diabetes Mellitus at the Telaga Dewa Community Health Center in Bengkulu City. It is recommended that patients with Type II Diabetes Mellitus pay more attention to their psychological well-being, implement stress management, and undergo regular health check-ups to help maintain controlled blood sugar levels.